Online Grocery Shopping Intentions: A Comparative Study between Gen Millenials and Gen Z in Indonesia - Felicia Vionita; Roger Alexsander Siburian (Jurnal Indonesia Sosial Teknologi, 2024)
This study focuses on behavioral intentions in buying groceries Online. This research also aims to compare the factors influencing Gen Millennial and Gen Z consumers. This research applies the Technology Acceptance Model (TAM). The hypotheses used are perceived usefulness, perceived ease of use, and perceived enjoyment of online grocery shopping. This research uses a survey to collect data from 199 respondents, 98 are millennials and 101 are Gen Z in Indonesia. The results showed that perceived usefulness and perceived enjoyment have a significant effect on online grocery shopping intentions in Gen Millennials and Gen Z, while perceived ease of use only affects online grocery shopping intentions in Gen Millennials.